2019
DOI: 10.1111/nmo.13703
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal distension after eating lettuce: The role of intestinal gas evaluated in vitro and by abdominal CT imaging

Abstract: BackgroundSome patients complain that eating lettuce, gives them gas and abdominal distention. Our aim was to determine to what extent the patients' assertion is sustained by evidence.MethodsAn in vitro study measured the amount of gas produced during the process of fermentation by a preparation of human colonic microbiota (n = 3) of predigested lettuce, as compared to beans, a high gas‐releasing substrate, to meat, a low gas‐releasing substrate, and to a nutrient‐free negative control. A clinical study in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Abdominal distension was related to a descent of the diaphragm with redistribution of normal abdominal contents. Using a biofeedback technique [ 30 ], patients learned to control the activity of the abdominal walls, and thereby prevented lettuce-induced distension [ 84 ]. Thus, abdominal distension in these patients is a somatic behavioral response, but why, in the first place, they acquired their belief and the mechanisms by which lettuce induces the abnormal response are not known.…”
Section: Conditioning Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal distension was related to a descent of the diaphragm with redistribution of normal abdominal contents. Using a biofeedback technique [ 30 ], patients learned to control the activity of the abdominal walls, and thereby prevented lettuce-induced distension [ 84 ]. Thus, abdominal distension in these patients is a somatic behavioral response, but why, in the first place, they acquired their belief and the mechanisms by which lettuce induces the abnormal response are not known.…”
Section: Conditioning Factorsmentioning
confidence: 99%
“…Bloating is a subjective sensation of abdominal pressure/fullness, is a subjective sensation of abdominal distension, andinvolves an objective increase in girth [ 53 ]. While bloating is a visceral sensation related to hypersensitivity, abdominal distention is a behavioural somatic response, featuring diaphragmatic contraction and descent coupled with relaxation and protrusion of the anterior abdominal wall [ 28 , 30 , 84 ]. The relation between bloating and distention is not clear, but conceivably, the sensation of bloating triggers the somatic behavioural response leading to distention, and in turn, the somatic response worsens bloating sensation.…”
Section: Other Factors Inherent To the Individualmentioning
confidence: 99%
“…It has been consistently shown that patients complaining of abdominal distension exhibit an objective increase in girth [ 2 ]. Abdominal distention is a behavioural somatic response featuring diaphragmatic contraction and descent coupled with relaxation and protrusion of the anterior abdominal wall [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This notion may be contestable, and bloating is not the same as flatulence, nor is it exclusively due to "a build-up of gas." 3,4 Regardless, the results of the trial will be welcome to many patients with bloating, which is notoriously difficult to manage. FMT was associated with symptom relief in about one-half of patients compared with about one-quarter of those receiving placebo (autologous stool).…”
mentioning
confidence: 99%
“…FMT is also being investigated as a therapeutic treatment in several other human conditions, including inflammatory bowel disease, irritable bowel syndrome, liver and kidney disease, and obesity/metabolic syndrome. 4 Most FMT clinical trials use allogenic transplants, that is, fecal material obtained from a healthy donor and transplanted into a recipient either by enema, endoscopy, or in an encapsulated form. Conversely, autologous transplants, which are prepared from the patient's own fecal material, are frequently used as placebo therapy.…”
mentioning
confidence: 99%